Peer pressure and psychological well-being among adolescents - Ichwani, Fitari Zakiyah; Grafiyana, Gisella; Rahardjo, Pambudi; Mildaeni, Itsna Nurrahma (Universitas Sarjanawiyata Tamansiswa, 2024)
During adolescence, there is a shift in life priorities from parents to peers. Peer groups significantly influence adolescents' socialization, and the demands they place on adolescents sometimes transform into cross-pressures that manifest as stress. Perceived stress can act as a trigger for pressure on psychological well-being. This research explores the correlation between peer pressure and psychological well-being among adolescents. The independent variable in this study is peer pressure, measured using a modified version of the Peer Pressure Scale (Cronbach's coefficient alpha = 0.910). The dependent variable is psychological well-being, measured using a modified version of the Psychological Well-Being Scale (Cronbach's alpha = 0.770). The sample comprises 263 students aged 18-21 years at Universitas in Purwokerto. The research employed a quantitative approach, and the data analysis technique used Pearson's Product Moment Correlation. The results of this study reveal a Pearson's Product Moment Correlation value of -0.249, with a significance value (p) of 0.000 (p 0.05). This indicates a negative correlation between peer pressure and psychological well-being. The findings suggest that the higher the level of peer pressure experienced by adolescents, the lower their psychological well-being tends to be, and vice versa.